To guide or not to guide? Quantitative monetary policy tools and macroeconomic dynamics in China - Hongyi Chen; Michael Funke; Ivan Lozev; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
This paper discusses the macroeconomic effects of China's informal banking regulatory tool "win-dow guidance," introduced in 1998. Using an open-economy DSGE model that includes the com-mercial banking sector, we study the stabilizing effects of this non-standard quantitative monetary policy tool and the implications of quantity-based vs. price-based monetary policy instruments for welfare. The analyses are relevant to the current overhaul of Chinese monetary policy.
URN:NBN:fi:bof-201702271168
Keywords: C61; E32; E44; E52; 330